Poemas para ler com palmas, de Edimilson de Almeida Pereira: uma proposta de letramento literário e racial nas aulas de língua portuguesa e literatura do Ensino Fundamental - Eliéverton Cristiano dos Santos (2023)
The present work focuses on how literary texts produced by black Brazilian authors are neglected when teaching Portuguese language and literature to students in elementary school. Moreover, this work analyses the presence and representations of black people in literature, the national literary canon, and literature education. The main objective refers to the proposition, from the literary work Poemas para ler com palmas, by Edimilson de Almeida Pereira, of paths for building teaching activities to develop literary and racial literacy in the Portuguese language classes of Primary Education. Thus, the research explores the potential that literary texts produced by black authors have of eliciting reflections that point to the construction of non-racist and antiracist educational practices without reducing the literary text to a mere thematic discussion, but encompassing all aspects of the text, including the aesthetic ones and, through the literary text, build didactic propositions aimed at structuring a process of literary and racial literacy. The reflections developed in this research aim to enable students, in Portuguese language and literature classes, to access diverse texts by different authors, especially black authors, and to positively resignify the presence and representation of blacks in literature. It is intended that teachers have materials to inspire them to build practices of literary literacy, understanding that literature must have a privileged space in the schooling of students and, at the same time, offer instruments for building non-racist and antiracist educational practices.